Avaliação do desempenho de coelhas alimentadas com farelo de canola em substituição parcial ou total ao farelo de soja - Scapinello, Cláudio; Lage, Ligia Vieira; Prado, Ivanor Nunes do (Acta Scientiarum. Animal Sciences, 2008)
The effect of partial and total substitution of soybean meal crude protein (SBM) by canola meal (CM) on live weight (LW), daily weight gain (DWG), daily feed intake (DFI) and feed conversion (FC) in female rabbits are provided. Rabbits were evaluated from weaning period (43 days of age) to adult life when they are capable of reproduction (150 days of age). Forty-eight White New Zealand females were used and distributed in four treatments. SBM was substituted at 00%, 33%, 66% and 100% levels by CM. The partial or total substitution of SBM by CM did not change (P > 0.05) the LW after 70 days old. Dunnett’s test showed that, independently of substitution level, FC of animals fed on meal with 33% SBM substitution by CM from age 43 to 90 days and 43 to 150 days was worse than that of animals fed on reference meal. LW120, DWG of 43 – 120-day-old animals receiving 33% SBM substitution by CM and LW150 and DWG of 43 – 150-day-old animals receiving meal with SBM substitution by 33% and 66% of CM were lower than those for animals that received reference meal. Excluding the reference meal, SBM substitution by CM during the periods in which animals were 43 - 120 days old and 43 - 150 days old caused an increase of DFI. Independently of level of inclusion as a substitute for SBM, results show that CM worsened the animals’ performance.